Melanogenic factors: regulation of gene expression - Vachtenheim, J; Duchon, J (Sbornik lekarsky, 1996)
Melanogenesis is a multistep biochemical process resulting in the formation of melanin in pigment cells in the skin and the eye. Three melanogenic factors, tyrosinase, TRP1, and TRP2 participate in the pathway. Here, the regulation of gene expression of these melanocyte-specific markers is shortly reviewed.
Keywords: intramolekulární oxidoreduktasy; Isomerases; proteiny; Gene Expression Regulation; membránové glykoproteiny; Intramolecular Oxidoreductases; Transcription, Genetic; Melanins; genetická transkripce; regulace genové exprese; oxidoreduktasy; Membrane Glycoproteins; zvířata; Humans; Oxidoreductases; tyrosinasa; melaniny; Monophenol Monooxygenase; isomerasy; Proteins; lidé; Animals